THE DIVERSITY AND DISTRIBUTION OF USEFUL PLANTS IN THE HOME GARDEN OF INDONESIAN CHRISTIAN UNIVERSITY (UKI) CAMPUS, CAWANG, EAST JAKARTA - Silalahi, Marina (Jurnal Biologi Udayana; Vol 20 No 2 (2016): Jurnal Biologi, 2016)
Home gardens are rich in biodiversity, including landscape in campus. The research was conducted on April-July2015. The research aimed to know the diversity and distribution of useful plants in home gardens of IndonesianChristian University (UKI) campus, Cawang-East Jakarta. The home gardens of UKI are divided into 7 locations.Inventaritation were conducted in all locations. The plants were observed, counted, recorded for its local nameand made its voucher specimens. The similarity index was calculated by Jaccard (Ji). Results found 96 speciesbelonged to 85 genera and 36 families of useful plants in UKI home gardens. Those plants used for shading area,fruits and ornamental plants. Arecaceae and Euphorbiaceae are families with the highest number of species (11and 9), respectively. The similarity index of plants was 0.07 to 0.49 in each location.
Keywords: home garden, diversity, distribution, Universitas Kristen Indonesia(UKI)